1994
DOI: 10.3758/bf03210950
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned reinforcement: Neglected or outmoded explanatory construct?

Abstract: The construct of conditioned reinforcement has been challenged over the past two decades, both as an adequate explanation of behavior in various situations (e.g., behavioral chains) in which it was previously regarded as crucial and in terms of the validity of the concept of conditioned value on which it is based. Recent research is reviewed that answers these criticisms and vindicates the importance ofthe construct. Also discussed are unanswered empirical issues regarding the concept and its implications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 56 publications
7
121
0
4
Order By: Relevance
“…That is, the conditioned reinforcement properties of the middle-link stimuli could be due in part to the time to food signaled by their onset and by the time to the terminal-link stimulus. Such a dual-process view is consistent with a variety of other data (e.g., Williams, 1994b), including those presented in Experiment 1.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…That is, the conditioned reinforcement properties of the middle-link stimuli could be due in part to the time to food signaled by their onset and by the time to the terminal-link stimulus. Such a dual-process view is consistent with a variety of other data (e.g., Williams, 1994b), including those presented in Experiment 1.…”
Section: Discussionsupporting
confidence: 75%
“…The question posed is how the stimuli that intervene between the choice and outcome modulate this control by the delayed discrimination contingencies. Several different, and sometimes opposing, effects (e.g., conditioned reinforcement, blocking, marking, bridging) have been postulated in different situations (see Williams, 1994b, for a discussion).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the same stimulus is present in all links (tandem schedule), or if the six different stimuli are presented in random order (scrambled-stimuli chains), performance is maintained in all links and the overall reinforcement rate is close to the maximum possible (6I, where I is the interval length). Other studies have reported very weak responding in early components of a simple chain fixed-interval schedule (e.g., Catania et al 1980, Davison 1974, Williams 1994review in Kelleher & Gollub 1962). These studies found that chains with as few as three fixed-interval 60-s links (Kelleher & Fry 1962) occasionally produce extreme pausing in the first link.…”
Section: Chain Schedulesmentioning
confidence: 99%
“…Many experimental and theoretical papers on conditioned reinforcement in pigeons and rats have been published since the early 1960s using some version of the concurrent chains procedure of Autor (1960Autor ( , 1969. These studies have demonstrated a number of functional relations between rate measures and have led to several closely related theoretical proposals such as a version of the matching law, incentive theory, delay-reduction theory, and hyperbolic value-addition (e.g., Fantino 1969a,b;Grace 1994;Herrnstein 1964;Killeen 1982;Killeen & Fantino 1990;Mazur 1997Mazur , 2001Williams 1988Williams , 1994Williams , 1997. Nevertheless, there is as yet no theoretical consensus on how best to describe choice between sources of conditioned reinforcement, and no one has proposed an integrated theoretical account of simple chain and concurrent chain schedules.…”
Section: Concurrent-chain Schedulesmentioning
confidence: 99%